Penggunaan Software Cabri 3D untuk Meningkatkan Kemampuan Spasial Siswa Sekolah Menengah Pertama - Yuli Ariani; Rahmah Johar; Marwan Marwan (Universitas Syiah Kuala, 2019)
Geometry is one of the materials that are considered important in mathematics with the aim that students gain confidence regarding math skills, be excellent problem solvers, and can communicate and reason mathematically. Geometry is a branch of mathematics closely related to spatial ability, the ability to visualize an image, recognize shapes and objects accurately, make changes to an object in his mind and recognize the difference, describes an object in mind and turn it into a tangible form, reveals the data in graphical form as well as sensitivity to relationships, color, line, shape, and space. This study focused on improving spatial skills based on research conducted by Olkun (2003), the ability to visualize the image, including the ability to mentally rotate and flip through 2D and 3D objects quickly and precisely. This research used a quasi-experimental design with pretest-postest group design. The instrument was used in the form of spatial ability tests. Population in this research was Year 8 students in one of the junior high school in Banda Aceh, and selected samples were the students from one of the classroom. The data analyzed in that the data pre-test and post-test spatial ability, using the t-test for data pairs. The result showed that the spatial ability of students after being given a lesson with the help of Cabri 3D software better than before given the spatial ability of students learning with the help of Cabri 3D software.